Edukasi Swamedikasi Pemilihan Obat Batuk Pilek Dalam Upaya Peningkatan Pengetahuan Masyarakat - VIANY ANGGI; Mariyani; Hana Kenta (CV. Multi Kreasi Media, 2022)
Community service activities have been carried out in the Prosperous Village, Palolo District, Sigi Regency, Central Sulawesi with the theme of self-medication education. This community service activity aims to provide education to the community about self-medication in the selection of cough and cold medicines as an effort to increase public knowledge in the Sejahtera Village. The methods used in service activities are counseling methods, free health checks and distribution of basic necessities to communities affected by flash floods in Sejahtera village. The results obtained from service activities, namely the Sejahtera village community can understand the concept of choosing cough and cold medicines in self-medication, it can be seen by evaluating the percentage level of community understanding after self-medication counseling activities in the selection of cough and cold medicines obtained results of 90%, which before the activity was carried out service was only obtained by 10%, in addition to that free health checks were carried out after the flash flood disaster experienced by the people of Sejahtera village, Palolo sub-district, Sigi district, Central Sulawesi and besides that the community also received food distribution at the end of the service activity. From the community service activities carried out in the Sejahtera village, it is hoped that the community will be able to better understand the selection of drugs for self-medication, especially for coughs and colds that often occur in this pandemic era.